Early Numeracy Challenges and Interventions for Students with Down Syndrome: A Scoping Review - Md Fauzy, Siti Intan Farahana; Hosshan, Hasrul (Jurnal Pendidikan Bitara UPSI, 2023)
Numeracy refers to the ability to solve basic mathematical operations, understand simple mathematical ideas, and apply mathematical knowledge and skills in daily life. Most special education students, especially those with Down syndrome, have difficulty mastering numeracy. There are various interventions that have been discussed by researchers around the world to address the problem of the level of numeracy comprehension of special education students. Therefore, this article focuses on the challenges and interventions involved in numeracy for special education students, especially those with Down syndrome. This study uses the scoping review method to obtain data based on challenges and interventions in numeracy. A total of six databases are used to search for articles according to the keywords that have been set. As a result of searching for these keywords, a total of 1771 articles were obtained. However, after the PRISMA screening process was implemented, only 44 articles were selected and coincided with the title of the study. Most articles show that Down syndrome students have difficulty understanding numeracy due to short-term memory. The teachers may be one of the factors that hinder students' understanding of numeracy because of their lack of expertise. Thus, teachers need to use students' existing knowledge or apply elements of daily life to give students an understanding of numeracy. Overall, the level of numeracy comprehension of special education students can be improved with the use of appropriate interventions. The study of numeracy comprehension in special education students needs to be increased, especially in Malaysia.